DWIFUNGSI TENTARA NASIONAL INDONESIA DAN ANCAMAN DEMOKRASI SERTA KEADILAN DALAM PERSPEKTIF PANCASILA - Aslan Noor; Anisa Estiyana; Sheren Elsila Wijaya; Rahayu Nur Meilani; Shady Shadana Muhammad Kirilofty; Nilna Salsabila (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The amendment to Article 47 in the revision of Law No. 34 of 2004 on the Indonesian National Armed Forces regarding active-duty soldiers' placement in civilian positions has sparked controversy, particularly regarding its alignment with the democratic and justice principles of Pancasila. This study examines how this revision affects civilian supremacy, civil-military relations, and Pancasila values, specifically the Fourth and Fifth Principles. This study employs a normative legal method combined with a descriptive-analytical approach, supported by Likert-scale questionnaires from 53 respondents selected via accidental sampling. Data were analyzed using descriptive statistics. The results indicate a high public urgency for meaningful participation in the revision process. However, the public expresses significant doubts regarding the transparency of the drafting and ratification processes, alongside the revision's alignment with Pancasila. Expanding military authority into the civilian sphere is perceived to threaten civilian supremacy, disrupt the bureaucratic merit system, and diminish career opportunities for civil servants. This study concludes that the revision does not yet fully reflect the principles of meaningful participation, legislative openness, and social justice as mandated by Pancasila as a staatsfundamentalnorm.